2020
DOI: 10.3390/ijms21124197
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Adeno-Associated Viral Vectors (rAAV)-Vector Elements in Ocular Gene Therapy Clinical Trials and Transgene Expression and Bioactivity Assays

Abstract: Inherited retinal dystrophies and optic neuropathies cause chronic disabling loss of visual function. The development of recombinant adeno-associated viral vectors (rAAV) gene therapies in all disease fields have been promising, but the translation to the clinic has been slow. The safety and efficacy profiles of rAAV are linked to the dose of applied vectors. DNA changes in the rAAV gene cassette affect potency, the expression pattern (cell-specificity), and the production yield. Here, we present a library of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 297 publications
(381 reference statements)
0
52
0
Order By: Relevance
“…Here, we further extended this concept by an in-depth analysis of various capsids linked to retinal gene therapy. The naturally occurring serotypes AAV2, AAV8, and the developed AAV2.7m8 were chosen, as they are currently applied in clinical trials or approved retinal therapy ( Buck and Wijnholds, 2020 ; Shahryari et al., 2019 ). Furthermore, AAV2.7m8 is a second-generation AAV developed via in vivo directed evolution, created and selected for more efficient delivery in ocular gene therapies ( Dalkara et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we further extended this concept by an in-depth analysis of various capsids linked to retinal gene therapy. The naturally occurring serotypes AAV2, AAV8, and the developed AAV2.7m8 were chosen, as they are currently applied in clinical trials or approved retinal therapy ( Buck and Wijnholds, 2020 ; Shahryari et al., 2019 ). Furthermore, AAV2.7m8 is a second-generation AAV developed via in vivo directed evolution, created and selected for more efficient delivery in ocular gene therapies ( Dalkara et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although gene therapies based on lentiviral and nonviral vectors delivery are in development, vectors derived from adeno-associated virus (AAV) are currently the most commonly used platform for delivery of ocular gene therapy. 4 , 5 Wild-type AAV is a small DNA virus with many naturally occurring capsid serotypes, which can be used directly for gene therapy or first intentionally modified. The virus is primarily non-integrating but persists as episomal DNA.…”
Section: Meeting Goals In the Context Of Ocular Gene Therapy History mentioning
confidence: 99%
“…One of the first approaches to show gene transfer in mouse retina used rAAV vectors to deliver a reporter gene by subretinal injection into an adult mouse retina [62]. Since then, AAV-mediated gene delivery into the retina has been used in several proof-of-concept studies to target photoreceptors or the RPE in mice and larger models (such as dogs) [63][64][65]. Notably, one of the studies involving the delivery of the RPE65 gene into mutant dogs showed therapeutic potential, which subsequently led to the approval of the first gene therapy drug (Luxturna TM ) by the Food and Drug Administration in 2018 [66].…”
Section: Viral Vectorsmentioning
confidence: 99%